Learning Pronunciation Using Record, Listen, Revise (RLR) Method in Dictionary Speech Assistant–ELSA Speak Application: How the Flow of Thinking Goes - Senowarsito Senowarsito; Agnesia Stefanny Susanto; Sukma Nur Ardini (Journal of Languages and Language Teaching, 2024)
Dictionary Speech Assistant is a combination of Record, Listen, Revise (RLR) method of ELSA Speak Application to help students improve their pronunciation. The aims of the research were to describe the effectiveness as well as to explore how the flow of thinking of the junior high students in improving their pronunciation using RLR method in ELSA Speak Application. An explanatory sequential mixed-method design was utilized to collect quantitative and qualitative data. The data gained from pre-test, post-test, and documentation of single words which were collected from 34 students of SMA N 6 Semarang. Then, they were analyzed using SPSS program quantitatively and descriptive qualitative. The quantitative result outlined that there was significant difference on students’ pronunciation skill with t-test value was higher than t-table (9.117>2.035). The effectiveness was qualitatively proven using RLR method; Record phase with the score of 23%, Listening phase which was followed by imitating process. In the Revise phase, after two to five attempts the students got the score of 96%, which was an increase from the first attempt. It is concluded that Dictionary Speech Assistant is beneficial for students in learning pronunciation. The majority of students believed that Dictionary Speech Assistant creates a new environment to help students improve their pronunciation skills.